Formation and Usage of Babigo in Japanese - Rina Fitriana; Shigehiro Ohashi Tamaru (Universitas Diponegoro, 2021)
This research discusses the formation and use of babigo slang language by taking data sources on video footage of Saitou Kyouko as a babigo speaker on the Saitou Kyouko YouTube channel. The purpose of this study was to determine the formation and function of babigo. The method used in this research is qualitative method. A qualitative method is a research procedure that produces descriptive data in the form of words or speech of people and behaviors that can be observed. The data collection method uses the listening method, which is the method used to obtain data by listening to the use of the language. While the data analysis method uses descriptive methods which are research methods carried out based on the existing facts, so the results are describing the elements of language as it is. Based on the analysis of this research data, the author found 1) Babigo formation that inserts a single vocal syllable in each Japanese language syllable 2) The Function of babigo is used by young people as a secret language and can also be used as language games.